Analisis Efektivitas Penggunaan Aplikasi Whatsapp dalam Pembelajaran Online di Era Pandemi Covid-19 - Sudarto sudarto; Besse Nur Hikma; Muliadi Muliadi (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this study was to determine the effectiveness of using the WhatsApp application in online learning for fourth grade students at SDN 139 Sakkoli, Sajoanging District, Wajo Regency in the Covid-19 Pandemic Era. Data was collected by means of in-depth interviews. Data reduction analysis techniques, data display, and conclusion drawing/verification. The effectiveness of the use of WhatsApp in online learning can be seen from six descriptors, namely, (1) students' motivation to participate in learning, (2) independence in completing assignments, (3) completion time of assignments/sending assignments, (4) quality of work done, (5) mastery of the material, (6) and character building. The results of this study indicate that the effectiveness of using the Whatsapp application in online learning for fourth grade students at SDN 139 Sakkoli, Sajoanging District, Wajo Regency in the Covid-19 Pandemic Era is quite effective, because of the 50% of students interviewed there were only four who had moderate motivation in learning using WhatsApp, four students did not do assignments independently, four students sent assignments according to the predetermined time limit, three students got grades according to predetermined standards and four students did not master the learning material that had been given by the teacher via whatsapp